The IASLC Lung Cancer Staging Project: Proposals for the Revision of the M Descriptors in the Forthcoming Eighth Edition of the TNM Classification of Lung Cancer. Issue 11 (November 2015) - Eberhardt, Wilfried E.E.; Mitchell, Alan; Crowley, John; Kondo, Haruhiko; Kim, Young Tae; Turrisi, Andrew; Goldstraw, Peter; Rami-Porta, Ramon
Abstract : Introduction: The aim of this study is to analyze all metastatic (M) categories of the current tumor, node, and metastasis (TNM) classification of lung cancer with the objective of providing suggestions for modifications of the M component in the next edition of the TNM classification for lung cancer. Methods: The new International Association for the Study of Lung Cancer lung cancer database was created from 94, 708 patients diagnosed as having lung cancer between 1999 and 2010. Including further patients submitted through the electronic data capture system to Cancer Research and Biostatistics until 2012, all together 1059 non–small-cell lung cancer cases were available for a detailed analysis of the clinical M categories. Overall survival was calculated using the Kaplan–Meier method, and prognosis was assessed using a Cox proportional hazards regression analysis. Results: No significant differences were found among the M1a (metastases within the chest cavity) descriptors. However, when M1b (distant metastases outside the chest cavity) were assessed according to the number of metastases, tumors with a single metastasis in a single organ had significantly better prognosis than those with multiple metastases in one or several organs. Conclusions: In this revision of the TNM classification, cases with pleural/pericardial effusions, contralateral/bilateral lung nodules, contralateral/bilateral pleural nodules, or a combination of multiple of these parameters should continue to be grouped as M1a category. Single metastatic lesions in a single distant organ should be newly designated to the M1b category. Multiple lesions in a single organ or multiple lesions in multiple organs should be reclassified as M1c category. This new division can serve as a first step into providing rational definitions for an oligometastatic disease stage in non–small-cell lung cancer in the future.